The Impact of Sleeve Gastrectomy on Hyperlipidemia: A Systematic Review - Khalid Al Khalifa; Ahmed Al Ansari; Abdul Rahim Alsayed; Claudio Violato (Journal of Obesity)
Background. Weight loss and reduction in comorbidities can be achieved by longitudinal sleeve gastrectomy (LSG). Existing evidence suggests that LSG resolves or improves hyperlipidemia in morbidly obese patients. The aim of this study was to systematically review the effect of LSG on hyperlipidemia. Methods. A systematic literature search was conducted from English-language studies published from 2000 to 2012 for the following databases: MEDLINE, EMBASE, CINAHL, PubMed, Clinical evidence, Scopus, Dara, Web of Sciences, TRIP, Health Technology Database, Cochrane library, and PsycINFO. Results. A total of 4,211 articles were identified in the initial search, and 4,185 articles were excluded based on the exclusion criteria. Twenty-six studies met the inclusion criteria for this systematic review, involving 3,591 patients. The mean preoperative body mass index (BMI) was 48±7.0 kg/m2 (range 37.2–65.3). The mean postoperative BMI was 35 ± 5.9 kg/m2 (range 26.3–49). The mean percentage of excess weight loss (EWL) was 63.1% (range 37.7–84.5), with a mean followup of 19.1 months (range 6–60). The mean levels of pre and post operative cholesterol were 194.4 ± 12.3 mg/dL (range 178–213) and 181 ± 16.3 mg/dL (range 158–200), respectively. Conclusion. Most patients with hyperlipidemia showed improvement or resolution of lipid profiles after LSG. Based on this systematic review, LSG has a significant effect on hyperlipidemia in the form of resolution or improvement in the majority of patients.